The OSCE in crisis - Dunay, Pál 1957- ([Chaillot papers] Chaillot paper, 2006)
The OSCE is in crisis. There can be no doubt but that the OSCE today, as compared to its heyday during the Cold War and in the mid-1990s, is a far less visible landmark on the European institutional landscape than was formerly the case. This Chaillot Paper seeks to take stock for an EU audience of the background and the evolution of the OSCE, the nature of the crisis which it is currently experiencing, the views of important participating states and the potential for the organisation's reform. The crisis of the OSCE matters to other actors of the European security environment for various reasons. Due to its distinctive composition (comprising 55 participating states from Europe and North America), it has a geographical reach that is more wide-ranging than that of other European and Euro-Atlantic institutions, and a broad security mandate. The OSCE is therefore an important actor on the European security scene at a time when most security problems extend beyond the traditional inter-state realm and notwithstanding the fact that other organisations - primarily the EU - are gradually extending their activity to the same field.